Strategi Komunikasi Pimpinan Dalam Menangani Konflik Internal Di IndiHome Branch Medan - Hayqal Baihaqie (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to describe leadership communication strategies in handling internal conflicts at IndiHome Branch Medan. Internal conflict is part of organizational communication dynamics that arises due to differences in perception, miscommunication, and differences in task understanding in the workplace. This study uses a qualitative approach with a descriptive research type to understand communication phenomena based on informants’ experiences. Data collection techniques were conducted through structured interviews with five informants consisting of one leader and four employees, supported by documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that leaders apply persuasive, dialogical, and situational communication strategies in handling internal conflicts. The communication process begins with clarification and information gathering, followed by direct discussions and two-way communication to achieve mutual understanding before making decisions. In addition, leaders utilize internal communication media to obtain initial information and apply one-way communication in certain situations that require quick and firm decisions. Thus, leadership communication strategies function not only to resolve conflicts but also to maintain communication stability and harmonious working relationships within the organization.This study aims to describe leadership communication strategies in handling internal conflicts at IndiHome Branch Medan. Internal conflict is part of organizational communication dynamics that arises due to differences in perception, miscommunication, and differences in task understanding in the workplace. This study uses a qualitative approach with a descriptive research type to understand communication phenomena based on informants’ experiences. Data collection techniques were conducted through structured interviews with five informants consisting of one leader and four employees, supported by documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that leaders apply persuasive, dialogical, and situational communication strategies in handling internal conflicts. The communication process begins with clarification and information gathering, followed by direct discussions and two-way communication to achieve mutual understanding before making decisions. In addition, leaders utilize internal communication media to obtain initial information and apply one-way communication in certain situations that require quick and firm decisions. Thus, leadership communication strategies function not only to resolve conflicts but also to maintain communication stability and harmonious working relationships within the organization.